Pengaruh Kualitas Produk Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Sebagai Variabel Intervening Pada Usaha Jahit Sepu’ta Di Kecamatan Rantepao Kabupaten Toraja Utara - Mey Enggane Limbongan; Wensy Senolinggi (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this study was to determine the significant effect of product quality on customer loyalty with customer satisfaction as an intervening variable in Sepu'ta Sewing Business in Rantepao District, North Toraja Regency. The type of research used is quantitative research with the sampling technique used, namely purposive sampling of 80 respondents, with testing using the SPSS application program. The data analysis technique used is a simple linear regression method. The results of this study indicate that product quality has a positive effect on customer satisfaction and customer loyalty. Likewise, the consumer satisfaction variable has a positive effect on customer loyalty. Furthermore, this study states that there is no effect of product quality on customer loyalty through customer satisfaction as an intervening variable. The direct effect of product quality is 0.419 greater than the indirect effect of customer satisfaction and customer loyalty 0.282. It is hoped that with the results of this research, the Sepu'ta Sewing Business will pay more attention to product quality so that it can increase the level of customer satisfaction and will also foster customer loyalty. In addition, it can improve product quality and other variables to determine which factors are more influential as other variables to determine which other factors are more influential as intervening variables on customer loyalty.